Factors influencing patient delay before primary percutaneous coronary intervention in ST-segment elevation myocardial infarction : the Stent for Life initiative in Portugal - Pereira, Hélder (2018)
© 2018 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. All rights reserved.